Ink adhesion failure during full scale offset printing: causes and impact on print mottle - Kamal Alm, Hajer; Ström, Göran; Schoelkopf, Joachim; Ridgway, Cathy; Gane, Patrick A.C. (Journal of Print and Media Technology Research, 2023)
The printing plate used in offset lithography is designed to accept ink on image areas and reject ink on non-image areas. In order to reject ink in conventional offset, fountain solution is needed to form a weak boundary layer between the plate and the ink. Paper and coated paper in particular are designed to accept ink and absorb ink oil and fountain solution. The latter is often transferred to the paper surface through the rubber blanket and its absorption or subsequent displacement is essential for final ink transfer to the surface. There are strong demands on the uniformity of the paper surface, including in respect to absorptivity, both in structure and chemistry, in order to gain a print of high quality. If this is not the case, the ink film thickness may be non-uniform; subsequently, ink adhesion may even fail completely, leaving white spots on the paper surface in the print. This gives rise to print mottle, a severe print quality defect. The aim of this paper was to study the quality of prints from a full scale offset printing trial made on pilot coated paper, with attention given to ink-surface adhesion. Seven calcium carbonate pigment based coatings with different contents of pigment dispersing agent were included in this study. The work showed that a moderate over-dosage of dispersant significantly increased the ink adhesion failure and print mottle, mainly onprints from the later print units and especially at high fountain feed levels. These findings demonstrate the fundamental impact of fount level, surface chemistry and coating formulation on ink adhesion and thus also print mottle.